2011
DOI: 10.1007/s11130-011-0256-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative Effect of Melissa officinalis on Human Colon Cancer Cell Line

Abstract: Melissa officinalis L. (Lamiaceae) is consumed as a traditional herbal tea in the Mediterranean region. The cytotoxic effect of the 50% ethanolic and aqueous extract, determined by the MTT and NR assays, was evaluated in vitro on Human Colon Cancer Cell Line (HCT-116), using Triton 10% as positive control. The 50% ethanolic extract showed significant differences after 72 h of treatment, reducing cell proliferation to values close to 40%, even the lowest dose tested (5 μg/ml). In the MTT assay, the same extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 26 publications
(29 reference statements)
3
49
0
2
Order By: Relevance
“…According to the in-vitro cytotoxicity analysis, using MTT and NR assays, this plant found as very effective against human colon cancer cell line (HCT-116) (Encalada et al, 2011). M. officinalis is a plant, which has shown several types of biological activity.…”
mentioning
confidence: 99%
“…According to the in-vitro cytotoxicity analysis, using MTT and NR assays, this plant found as very effective against human colon cancer cell line (HCT-116) (Encalada et al, 2011). M. officinalis is a plant, which has shown several types of biological activity.…”
mentioning
confidence: 99%
“…For example, a recent study by Karthik kumar et al, showed that RA supplementation reduced cell proliferation markers in 1,2-dimethylhydrazine (DMH)-induced rat colon carcinogenesis [30] and other studies in the last five years have described cytotoxic and anti-proliferative roles for RA in a number of other cancer cell types [19,[31][32][33]. In this study, initial experiments examined whether treatment with RA at concentrations ranging from 10-80 µg/ml, could reduce HNSCC cell numbers at 24 hrs.…”
Section: Ra Inhibits Hnscc Cell Viabilitymentioning
confidence: 99%
“…According to Bauman,8 in fruits, there are important nutrient besides other vitamins, minerals, flavonoids and phytochemicals, which have been reported as a good contributing factor to the health.In addition, epidemiological studies, including experiments performed on animal models and investigations on humans have proven that consumption of a diet rich in vegetables and fruits is associated with a low risk of contracting some diseases, including cardiovascular diseases and cancers. 9 The genus, L. domesticum corr. belongs to the family Meliaceae, and known locally as duku.…”
Section: Introductionmentioning
confidence: 99%